2018
DOI: 10.1038/s41598-018-29681-3
|View full text |Cite
|
Sign up to set email alerts
|

Runx1-Stat3-Tgfb3 signaling network regulating the anterior palatal development

Abstract: Runx1 deficiency results in an anteriorly specific cleft palate at the boundary between the primary and secondary palates and in the first rugae area of the secondary palate in mice. However, the cellular and molecular pathogenesis underlying such regional specificity remain unknown. In this study, Runx1 epithelial-specific deletion led to the failed disintegration of the contacting palatal epithelium and markedly downregulated Tgfb3 expression in the primary palate and nasal septum. In culture, TGFB3 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…From our previous results, the epithelial-specific elimination of Runx1 is known to be exhibited at the anterior cleft palate ( Sarper et al, 2018a , b ). It is also known that fewer TUNEL-positive cells were detected on the unfused epithelium in Runx1 mutants ( Sarper et al, 2018b ). We did not detect a significant reduction in the area of protruded cells in the cultured nasal septum of K14-Cre/Runx1 fl/fl mice in comparison to the control group ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…From our previous results, the epithelial-specific elimination of Runx1 is known to be exhibited at the anterior cleft palate ( Sarper et al, 2018a , b ). It is also known that fewer TUNEL-positive cells were detected on the unfused epithelium in Runx1 mutants ( Sarper et al, 2018b ). We did not detect a significant reduction in the area of protruded cells in the cultured nasal septum of K14-Cre/Runx1 fl/fl mice in comparison to the control group ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 92%
“…The present and previous findings suggest that the induction of extrusion is critical for the fusion of facial processes and that it can be inhibited by Runx1 depletion ( Martínez-Alvarez et al, 2000 ; Takigawa and Shiota, 2004 , 2007 ; Charoenchaikorn et al, 2009 ; Hu et al, 2015 ). Importantly, our previous report showed that the excision of Runx1 in epithelial tissues takes place at the beginning of explant culture ( Sarper et al, 2018a , b , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations